Answer:
Step-by-step explanation:
Here, we want to get the plot of the parabola
We start by getting its vertex
We have that as follows:
![\begin{gathered} f(x)\text{ = (-x+3)(x+5)} \\ f(x)=-x^2-2x+15 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/eqlsfcv0qaxhydolt0n715dhvh7clywe8v.png)
We have the vertex form as follows:
![\begin{gathered} f(x)\text{ = }-1(x+1)^2+16 \\ \text{compared with the general vertex form:} \\ f(x)=a(x-h)^2+k \\ \text{vertex is (h,k)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ruxltwafcqtic44n8nr8i5cw66k8b52obn.png)
The vertex here is thus (-1,16)
To get the other point, we can equate the values in the brackets to zero and solve for x
We have that as:
![\begin{gathered} -x+3\text{ = 0} \\ x\text{ = 3} \\ x+5\text{ = 0} \\ x=\text{ -5} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jw1gon6j50fb2dnna99hixg1b4kpygxyck.png)
The other points are thus (3,0) and (-5,0)
Thus, we can join (-1,16) with either (3,0) and (5,0) as shown below: